Pengaruh Islamic Branding, Islaminc Adevertising, dan Kualitas Produk Terhadap Keputusan Pembelian di Konveksi Helmi Busana Muslim Tulungagung - Agus Eko Sujianto; M Khoirul Amilin (Jurnal Iqtisaduna, 2023)
This research aimed to validate te effect of islamic branding, islamic advertising and product quality on purchasing decisions. The approach in this research used quantitative and data collection methods by distributing questionnaries and supporting data collected trough documentation techniques. Respondents from this study were 50 business consumers of muslim fashin helmi convection. This research was an analytical technique using validity test, reability test, normality test, multicoleniarity test, heteroscedasticity test, F-test, T-test, and the coefficient of determination. The results of this research indicated that the test material data can be said to be valid and can be proven by testing the validity. The conclusion from the calculation of the data shows an insignificant positive value between the Islamic branding variable (x1) on the purchasing decision variable (y) but there is a significant positive between the Islamic advertising variable (x2) and product quality (x3) on the purchasing decision variable (y). this is proven by multiple linear regression test and T test. The results obtained show Islamic advertising and product quality can be used as a strategy to form and maintain purchasing decisions.